Development of a Methodology for Joining Technology Selection based on Cost Information in the Preliminary Automotive Body-in-White Product Development Process - Stahl, Jan (Cranfield University, 2008)
The substantial demand of the customer for the conservation of natural resources and of the environment puts pressure on the automotive industry to reduce fuel consumption and emissions. One response to this challenge is to reduce car body weight. Hence car body development has shown an increase in the use of light weight materials that demand new production methods and joining technologies. Accordingly car body engineers have progressively less time to assess the manufacturing cost of an increasing number of new design concepts with new material and corresponding joining techniques. A review of the pertinent literature shows that there is no established methodology enabling automotive body engineers to make a rough manufacturing cost estimate of different new design concepts in the early phase of the Product Development Process. The aim of the present thesis is to provide car body engineers with a cost estimating methodology that makes it possible for them in the preliminary phase of the design process to estimate the manufacturing cost of new design concepts more systematically, hence more reliably, thus enhancing cost reduction. The methodology is based on the notion of Standardised Working Contents, which, as fundamental units of work, enable designers to compare the financial requirements of various new design options with greater facility and greater accuracy. Furthermore the methodology identifies the most cost efficient Joining Technique combination with a high degree of reliability. Economical and technical data required for the methodology are gathered from an industrial survey in collaboration with the design, planning, finance and manufacturing departments of a leading automotive company. Dynamic Programming taken from the area of Operations Research is employed to provide the optimal Joining Technique combination in terms of manufacturing cost of the car body design concept under scrutiny. Results obtained from an automotive industrial case study confirm the effectiveness of the methodology while pointing out its limitations and possibilities.